Effectiveness of robotic balance training on postural instability in patients with mild Parkinson's disease: A pilot, single blind, randomized controlled trial - Stefania Spina; Salvatore Facciorusso; Nicoletta Cinone; Raffaella Armiento; Alessandro Picelli; Christian Avvantaggiato; Chiara Ciritella; Pietro Fiore; Andrea Santamato (Medical Journals Sweden, 2021)
Objective: To examine whether tailored robotic platform training could improve postural stability compared with conventional balance treatment in patients with mild Parkinson's disease.  Design: Randomized single-blind pilot study. Subjects: Twenty-two patients with mild Parkinson's disease (Hoehn and Yahr scale; H and Y 1-2). Methods: Patients were randomly assigned to an experimental group for robotic balance training and to a control group for conventional balance training. Each patient received 20 treatments (45 min/session, 5 times/week). Blinded evaluations were conducted before and after the treatment and 1 month post-treatment. Primary outcome measures were Mini BESTest, and Berg Balance Scale; secondary outcome measures were 10-Meter Walk Test, Five Times Sit to Stand Test, and Parkinson's Disease Questionnaire 39. Results: Primary outcome measures in patients in both the experimental and control groups improved significantly after the balance treatment. Similar results were found for all the secondary outcome measures. The experimental group performed significantly better than the control group at both post-intervention and follow-up evaluation in the primary outcomes (p < 0.05). No significant differences be-tween groups were found in secondary outcomes. Conclusion: Robot-assisted balance training may be a promising tool to improve postural stability in patients with mild Parkinson's disease.